Combined motor point associative stimulation (MPAS) and transcranial direct current stimulation (tDCS) improves plateaued manual dexterity performance - Hoseini, Najmeh; Munoz-Rubke, Felipe; Wan, Hsuan-Yu; Block, Hannah J. (Neuroscience letters, 2016)
•We asked if combining central and peripheral stimulation could improve hand dexterity without motor practice.•Subjects were healthy young adults and had already reached plateau on a manual dexterity task.•Combining anodal tDCS with MPAS significantly improved manual dexterity beyond the ceiling of performance.•Central tDCS to complement peripheral MPAS may be a promising avenue of treatment for patients with impaired hand dexterity. Motor point associative stimulation (MPAS) in hand muscles is known to modify motor cortex excitability and improve learning rate, but not plateau of performance, in manual dexterity tasks. Central stimulation of motor cortex, such as transcranial direct current stimulation (tDCS), can have similar effects if accompanied by motor practice, which can be difficult and tiring for patients. Here we asked whether adding tDCS to MPAS could improve manual dexterity in healthy individuals who are already performing at their plateau, with no motor practice during stimulation. We hypothesized that MPAS could provide enough coordinated muscle activity to make motor practice unnecessary, and that this combination of stimulation techniques could yield improvements even in subjects at or near their peak. If so, this approach could have a substantial effect on patients with impaired dexterity, who are far from their peak. MPAS was applied for 30min to two right hand muscles important for manual dexterity. tDCS was simultaneously applied over left sensorimotor cortex. The motor cortex input/output (I/O) curve was assessed with transcranial magnetic stimulation (TMS), and manual dexterity was assessed with the Purdue Pegboard Test. Compared to sham or cathodal tDCS combined with MPAS, anodal tDCS combined with MPAS significantly increased the plateau of manual dexterity. This result suggests that MPAS has the potential to substitute for motor practice in mediating a beneficial effect of tDCS on manual dexterity.